2021
DOI: 10.1155/2021/6894278
|View full text |Cite
|
Sign up to set email alerts
|

A Transcription Factor-Based Risk Model for Predicting the Prognosis of Prostate Cancer and Potential Therapeutic Drugs

Abstract: Background. Prostate cancer (PC) is one of the most critical cancers affecting men’s health worldwide. The development of many cancers involves dysregulation or mutations in key transcription factors. This study established a transcription factor-based risk model to predict the prognosis of PC and potential therapeutic drugs. Materials and Methods. In this study, RNA-sequencing data were downloaded and analyzed using The Cancer Genome Atlas dataset. A total of 145 genes related to the overall survival rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…A study conducted in China over a 24-year period revealed that ESCC constituted around 95% of esophageal cancer cases in the country, whereas the incidence of EAC was relatively low. However, due to rapid economic growth and the adoption of more Westernized diets and lifestyles, the occurrence of EAC has been increasing annually in both urban and rural areas of China (Rai et al, 2023;Luo et al, 2021;Liang et al, 2017). This trend necessitates the attention of researchers in cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in China over a 24-year period revealed that ESCC constituted around 95% of esophageal cancer cases in the country, whereas the incidence of EAC was relatively low. However, due to rapid economic growth and the adoption of more Westernized diets and lifestyles, the occurrence of EAC has been increasing annually in both urban and rural areas of China (Rai et al, 2023;Luo et al, 2021;Liang et al, 2017). This trend necessitates the attention of researchers in cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In line with these findings, this study showed that it was functionally implicated in myofibril formation, adhesive spots, and the development of muscular structure. Prior studies found that CACNA2D1 played a certain role in the carcinogenesis of prostate cancer [45], bladder cancer [46], epithelial ovarian cancer [47], laryngeal squamous cell cancer [48], gastric cancer [49], non-small-cell cancer [50], and other cancers, but very few studies examined the association between CACNA2D1 and BC. Meng Li et al showed that the cells overexpressing α2δ1 were involved in the self-renewal, differentiation, invasion, and metastasis of the tumor.…”
Section: Discussionmentioning
confidence: 99%
“…treatment of PCa bone metastases [29].The development of many cancers involves dysregulation or mutations in key transcription factors. Ruixiang Luo et al established a risk model based on transcription factors to predict that the prognosis of PCa may be related to immune disorders, and SPOP, TP53 and TTN may be potential targets of PCa prognosis [30].PD-1/PD-L1 checkpoint inhibitors such as pembrolizumab and durvalumab enhance the T cell response by inhibiting receptor and ligand binding, stimulating the body's immune system to attack tumor cells [31].Immunomodulatory drugs, such as lenalidomide and Taquinomide, can improve the tumor microenvironment and enhance the anti-tumor immune response.These results all suggest that the single factor we constructed the model has an important correlation with the occurrence and development of tumors.…”
Section: Declarations Ethical Approvalmentioning
confidence: 99%